Medical treatment of perianal crohn disease - Al-Ghamdi Abdullah (The Saudi Journal of Gastroenterology, 2002)
Crohn disease is a chronic illness that affects the gastrointestinal tract from the mouth to the anus. Perianal Crohn develops in 31-94% of patients over the course of their illness. It affects the skin in the perianal area, the anal canal and can cause fistulae. It is diagnosed clinically and by other modalities like endoscopy, barium CT scan, endoscopic sonography and magnetic resonance image examination. The treatment of perianal Crohn disease is either medical or surgical. The current medical treatment will be reviewed in this article